ORGANIZATIONAL AND INSTITUTIONAL FOUNDATIONS OF DEPOSIT OPERATIONS BY COMMERCIAL BANKS - Shamsiev Nоdir Muratovich (Modern American Journals, 2025)
This paper examines the organizational and institutional foundations of deposit operations of commercial banks, which are the most important element of banking activities. Theoretical aspects of deposits, their classification and role in the formation of the resource base of banks are studied. Organizational mechanisms for conducting deposit operations, internal control procedures and risk management are analyzed. Particular attention is paid to institutional factors influencing the deposit market, including the role of the Central Bank and public policy. Modern trends and innovations that contribute to the development of deposit services are considered. Based on the analysis, recommendations are given for improving the deposit activities of commercial banks. The work can be useful for specialists in the banking sector and financial market researchers.
Keywords: Deposit operations, commercial banks, organizational framework, institutional aspects, deposit, banking system, regulation, Central Bank, risks, innovations, financial stability